New evolutionary insights into the non-enzymatic origin of RNA oligomers - Šponer, Judit E; Šponer, Jiří; Mauro, Ernesto Di (Wiley interdisciplinary reviews. RNA, 2017)
We outline novel findings on the non-enzymatic polymerization of nucleotides under plausible prebiotic conditions and on the spontaneous onset of informational complexity in the founding molecule, RNA. We argue that the unique ability of 3', 5' cyclic guanosine monophosphate to form stacked architectures and polymerize in a self-sustained manner suggests that this molecule may serve as the 'seed of life' from which all self-replicating oligonucleotides can be derived via a logically complete sequence of simple events. WIREs RNA 2017, 8:e1400. doi: 10.1002/wrna.1400 For further resources related to this article, please visit the WIREs website.
Keywords: Animals; lidé; Oligonucleotides; zvířata; původ života; oligonukleotidy; RNA; Evolution, Molecular; molekulární evoluce; Origin of Life; Humans